Gendered approaches to spatial development in Europe. Perspectives, similarities, differences. - (:unkn) unknown (Routledge, 2019)
This book explores the extent to which gendered approaches are evident and effective in spatial development in selected European countries. Beginning with an introduction to theories and concepts of gender, space and development, the book includes a brief historical review of gender in spatial planning and development throughout Europe in general, and an overview of different national frameworks in European countries, comparing legal, organisational and cultural similarities and differences. This is followed by a critical reflection on how simplifications and stereotypes of gender concepts are used in the practice of spatial development. The main part of the book offers a transnational discussion of planning practices on selected thematic topics. It starts with gender-sensitivity in urban master planning and at neighbourhood level referring to different types of planning manuals. Furthermore, the book focuses on gender-sensitive evaluation in urban planning as well as international agendas for sustainable development as a framework for a new generation of gender equality policies. The chapter authors assert that climate change, migration and austerity have threatened gender equality and therefore spatial development needs to be especially alert to gender dimensions. The editors end with an outlook and suggestions for further action and research on gender issues in spatial development. With inputs from some of Europe s leading thinkers on gender, space and development, this volume is designed to inspire students, scholars and practitioners to reflect upon the contribution that gendered approaches can make in the various fields of spatial development and environmental planning.
Keywords: Stadtplanung; Raumplanung; Stadtteil; Stadtquartier; Nachhaltigkeit; Geschlechterrolle; Planungsprozess; Planungsinhalt; Internationaler Vergleich; Genderforschung